Systematic Transformation Development - Kühne, Thomas; Mezei, Gergely; Syriani, Eugene; Vangheluwe, Hans; Wimmer, Manuel (Electronic Communications of the EASST, 2009)
Despite the pivotal significance of transformations for model-driven approaches, there have not been any attempts to explicitly model transformation languages yet although a number of benefits are to be gained. First, transformation developers may change the design of their transformation languages by modeling, rather than programming. Second, they may use environments to create transformations that are customized with respect to the input and output languages involved. In this paper, we use a running example to identify, discuss, and demonstrate some of the above advantages. In particular, we explore and suggest ways to systematically support developers in creating transformation languages by means of semi-automated metamodeling.